Agriculture Distress and Farmers’ Suicide in Kerala in the Globalization Era - Sherin P S; Dr. Haseena V.A, (Indian Journal of Agriculture Engineering (IJAE), 2024)
Liberalization, privatization, and globalization are to blame for Kerala’s rural poverty and farmer suicides. Ineffective state and federal government policies, a lack of coordinated public investment, ongoing flooding, trade manipulation, false seeds and pesticides, a fluctuating price for agricultural products, growing cultivation expenses, an increase in droughts, as well as a loss of biodiversity are all factors that negatively affect agriculture. Though it receives criticism, the opposition to the current administration is strong in states with high rates of farmer suicide. A.R. Vasavi’s Triple Crisis of Agriculture (1999), the widespread use of hybrid seeds, chemical fertilizers, and pesticides, as well as the inadvertent escalation of farmer debt, are the five primary debates that need to be addressed in order to investigate farmer suicides. As of now, a significant amount of government funding—1,69,6718 crores in 2017–18 and 97,3729 crores in the 12th five-year plan—was allocated to the agriculture sector. However, the state of farming and agrarian hardship has not much improved. However, the rate of agriculturalists’ concern dramatically increased. The price of the cash crop products grown in Kerala—pepper, coffee, and rubber—is significantly impacted by free trade agreements with ASEAN. Farmer’s suicide has a significant relationship with these factors as well as extreme climate change along with, the heavy burden of debt, marginalization of land, etc.